The Effects of Early Neglect on Cognitive, Language, and Behavioral Functioning in Childhood - Spratt, Eve G. (2012)
OBJECTIVES: Few studies have explored the impact of different types of neglect on children’s development. Measures of cognition, language, behavior, and parenting stress were used to explore differences between children experiencing various forms of neglect, as well as to compare children with and without a history of early neglect. METHODS: Children, ages 3 to 10 years with a history of familial neglect (USN), were compared to children with a history of institutional rearing (IA) and children without a history of neglect using the Differential Abilities Scale, Test of Early Language Development, Child Behavior Checklist, and Parenting Stress Index. Factors predicting child functioning were also explored. RESULTS: Compared with youth that were not neglected, children with a history of USN and IA demonstrated lower cognitive and language scores and more behavioral problems. Both internalizing and externalizing behavior problems were most common in the USN group. Externalizing behavior problems predicted parenting stress. Higher IQ could be predicted by language scores and an absence of externalizing behavior problems. When comparing the two neglect groups, shorter time spent in a stable environment, lower scores on language skills, and the presence of externalizing behavior predicted lower IQ. CONCLUSION: These findings emphasize the importance of early stable, permanent placement of children who have been in neglectful and pre-adoptive international settings. While an enriching environment may promote resilience, children who have experienced early neglect are vulnerable to cognitive, language and behavioral deficits and neurodevelopmental and behavioral evaluations are required to identify those in need of intervention.